2009
DOI: 10.1260/1747-9541.4.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Organisational Stressors, Coping, and Coping Effectiveness: A Longitudinal Study with an Elite Coach

Abstract: The purpose of this study was to examine organisational stressors, coping, and perceptions of coping effectiveness with an elite coach. The participant completed a daily diary over a 28-day period. Each diary entryconsisted of an open-ended stressor, a coping response section, and a Likert-type scale measure of coping effectiveness. Inductive and deductive content analysis procedures were used to analyse the diaries, in addition to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
82
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(92 citation statements)
references
References 21 publications
(47 reference statements)
8
82
0
2
Order By: Relevance
“…This substantial investment highlights the importance attached to producing and developing world class coaches in the United Kingdom. This growing importance afforded to coaching is reflected in an increase in the amount of sport psychology research dedicated to the topic (e.g., Erickson, Côté, & Fraser-Thomas, 2007;Frey, 2007;Levy, Nicholls, Marchant, & Polman, 2009;Olusoga et al, 2009;Thelwell, Weston, Greenlees, & Hutchings, 2008a;2008b). For example, the importance of the relationship between coach and athlete has been commented upon by a number of authors (e.g., Baker, Yardley, & Côté, 2003;Lyle, 1999), and coaches have been identified as having a significant impact on athletes' satisfaction and performance accomplishments (Jowett & Cockerill, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This substantial investment highlights the importance attached to producing and developing world class coaches in the United Kingdom. This growing importance afforded to coaching is reflected in an increase in the amount of sport psychology research dedicated to the topic (e.g., Erickson, Côté, & Fraser-Thomas, 2007;Frey, 2007;Levy, Nicholls, Marchant, & Polman, 2009;Olusoga et al, 2009;Thelwell, Weston, Greenlees, & Hutchings, 2008a;2008b). For example, the importance of the relationship between coach and athlete has been commented upon by a number of authors (e.g., Baker, Yardley, & Côté, 2003;Lyle, 1999), and coaches have been identified as having a significant impact on athletes' satisfaction and performance accomplishments (Jowett & Cockerill, 2003).…”
mentioning
confidence: 99%
“…It is therefore increasingly important to develop our understanding of coaches' coping strategies. To address this, Levy et al (2009), conducted a longitudinal study examining organizational stressors, coping strategies, and coping effectiveness with an elite coach. Administration (18.9% of all stressors reported), overload (12.9%) and athletes (8.6%) were the most frequent stressors cited and diary entries revealed 70 coping strategies used over a 28-day period.…”
mentioning
confidence: 99%
“…Table 1 provides an outline of the themes that emerged from the content analysis. The table does not include a frequency count of the different sources of strain (e.g., Hanton, Fletcher, & Coughlan, 2005;Levy, Nicholls, Marchant, Polman, Fletcher, & Hanin, 2009;Mellalieu, Neil, Hanton, & Fletcher, 2009) and the respective coping strategies (Weston et al, 2009) employed by the players. To conduct a frequency count, it would have been necessary to use a lessfluid interview procedure and this may have inhibited participant and interviewer interaction and the collection of rich narrative data.…”
Section: Discussionmentioning
confidence: 99%
“…The findings suggest that pay and job satisfaction alone are not enough to keep an individual in a position (Ryan & Sagas, 2009). Both coaches and athletic directors have been the subject of job-related stress research and both roles have a number of stressors and demands with which the professionals struggle (Levy, Nicholls, Marchant, & Polman, 2009). Frey (2007 reported that one of the major stressors in Division I coaching was the pressure associated with trying to accomplish too many obligations and responsibilities associated with their job.…”
Section: Personal Challenges Associated With Thementioning
confidence: 99%